The Immediate Effect of Sliding Cupping on those Suffering from Muscular Lower Back Pain among Workers at Mutah University (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
This study aimed to identify the immediate effect of sliding cupping as an immediate response to those suffering from muscular low back pain in relation to the following variables: the temperature of the right part in the lower back, the temperature of the left part in the lower back, the forward range of motion of the torso, and the backward range of motion of the torso  The experimental method was used as it suited the nature and objectives of the study, on a sample consisting of (13) people with mild lower back pain from workers at Mutah University who visited the health center. They were selected intentionally and subjected to one session of sliding cupping for a period of one minute. The researcher used tests as a tool for collecting data, and used the statistical package program (SPSS) to analyze the results and Wilcoxon analysis to compare the pre- and post-measurements.   The results indicated that there were statistically significant difference between the pre- and post- measurements in favor of the post measurement in terms of the temperature of the right part of the lower back, the temperature of the left part of the lower back, the range of motion of the torso forward, and the range of motion of the torso back.. The Researcher concluded that the  use of one session of cupping for one minute has a positive effect as an immediate response to to patients with mild muscular lower back pain. The Researcher recommended the need to conduct more follow-up similar studies at larger samples in order identify the duration of that immediate positive effect. It is also recommended to perform this type of cupping on cases of moderate and severe low back pain, as well as on non-specific low back pain of non-muscular origin. as well as to conduct more similar studies on all other kinds of  non-specific low back pain.
Keywords: Non specific Muscular Low Back Pains; Lowerer Back Temperature; Forward and Backward Range of Motion of the Torso